LINGUISTIC FEATURES OF METAPHORICAL AND EUPHEMISTIC EXPRESSIONS IN ENGLISH AND UZBEK LANGUAGES - Mehriddin Shakarboyev (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This paper investigates the linguistic features of metaphorical and euphemistic expressions in English and Uzbek languages, focusing on their semantic, pragmatic, and cultural functions. Metaphors serve as cognitive tools that reflect how speakers conceptualize abstract phenomena, while euphemisms function as polite substitutes for socially sensitive or taboo subjects. The study highlights the similarities and differences between the two languages in terms of metaphorical imagery, euphemism formation, and cultural values embedded in language use. Through comparative analysis, the paper reveals how metaphor and euphemism are shaped by national worldview, social norms, and communicative strategies. The findings contribute to a deeper understanding of intercultural communication, linguistic politeness, and translation challenges.